Making trust explicit in distributed commerce transactions - Ketchpel, S.P.; Garcia-Molina, H. (Proceedings of the 16th International Conference on Distributed Computing Systems, 1996)
In a distributed environment where nodes are independently motivated, many transactions or commercial exchanges may be stymied due to a lack of trust between the participants. The addition of trusted intermediaries may facilitate some exchanges, but others are still problematic. We introduce a language for specifying these commercial exchange problems, and sequencing graphs, a formalism for determining whether a given exchange may occur We also present an algorithm for generating a feasible execution sequence of pairwise exchanges between parties (when it exists). Indemnities may be offered to facilitate previously infeasible transactions. We show when and how they enable commercial transactions.